A case of inflammatory ascites. Issue 3 (June 2014) - Guidetti, E.; Galassi, M.; Croci, L.; Stagni, B.; Crespi, C.; Tovoli, F.; Bolondi, L.
Abstract : Case background: Ascites appears mainly as a consequence of portal hypertension in patients with liver cirrhosis, or can be caused by several other causes, such us congestive heart failure, peritoneal malignancy, or tuberculosis. In some cases, ascites can pose a diagnostic challenge for clinicians and in some patients, despite thorough and extensive work-up, the origin of this ascites remains unknown. Case report: In the unusual case hereby reported, a 52-year-old man developed severe ascites in a few weeks, in the absence of known liver disease or congestive hearth failure. We performed laboratory analysis, endoscopic, and imaging investigations, including abdominal contrast-enhanced computed tomography and 18-fluorodeoxyglucose-positron emission tomography. Peritoneal fluid analysis showed exudative fluid without neoplastic cells. A diagnostic laparoscopy with multiple diagnostic biopsies was carried out, but no macroscopic cause of the ascites was found; histopathological examination showed minimal aspects of diffuse and non-specific chronic inflammation. Conclusions: We decided to empirically treat the patient with steroid therapy (methylprednisolone: 0·5 mg/kg/day). Over a period of 6 weeks, his ascites resolved and at 2 months, he was in remission on low-dose methylprednisolone. Our final hypothesis was reactive inflammatory ascites. The literature on ascites and its management has also been reviewed.